Meningkatkan Pemahaman Bahasa Arab Melalui Analisis Teks Pendek di Madrarah Ibtidaiyah Nurul Hasan Kertosono Gading Probolinggo - Slama Slama; Ainur Rofiq Sofa (Lembaga Pengembangan Kinerja Dosen, 2025)
Arabic language learning at the Nurul Hasan Elementary School level has an important role in building a foundation of language understanding for students. However, one of the challenges faced by students is the lack of understanding in understanding Arabic texts effectively. This study aims to improve students' Arabic language understanding through the short text analysis method at the Nurul Hasan Elementary School Kertosono Gading, Probolinggo. The research method used is a qualitative approach with observation, interview, and documentation study techniques. The subjects of the study consisted of students in grades V and VI who had difficulty understanding Arabic texts. The results of the study showed that short text analysis helped students improve their language understanding, namely in terms of vocabulary, understanding sentence structure, and improving their ability to read and translate texts. This method has long been applied to grades V and VI before to produce a young generation who can develop foreign language skills. In addition, this method can also increase students' motivation in learning Arabic because of its more contextual and applicable approach. Thus, the use of short text analysis can be an effective strategy in improving Arabic language understanding at the Nurul Hasan Elementary School. It is hoped that this research can contribute to the development of Arabic language teaching methods that are more interactive and easy for students to understand.